A Conceptual Model of Islamic Religious Education Learning Based on Islamic Educational Philosophy: A Literature Review - Muhammad Abdul Aziz; Muhlisin Muhlisin; Rahmi Anekasari (Academicus: Journal of Teaching and Learning, 2026)
The advancement of technology and educational transformation has significantly influenced Islamic Religious Education (IRE) learning. Previous studies have generally examined Islamic educational philosophy, IRE learning strategies, and educational technology separately, resulting in limited research that integrates these dimensions into a comprehensive conceptual framework. This study aims to analyze Islamic educational philosophy from a contemporary educational perspective, identify the characteristics of IRE learning, and formulate its implications for the development of IRE learning strategies. This study employed a qualitative literature review design. Data were collected through a systematic search of publications indexed in Google Scholar, Dimensions, and the Directory of Open Access Journals (DOAJ) from 2022 to 2026. Of the 33 articles identified, 27 met the inclusion and exclusion criteria and were analyzed using content analysis. The findings indicate that Islamic educational philosophy remains relevant as a foundation for education because it promotes holistic human development through the integration of tawhid, fitrah, akhlaq, and insan kamil values. Contemporary IRE learning is characterized by student-centered approaches, diverse learning resources, active learning strategies, the integration of Islamic values, and the use of technology as a learning support tool. The study reveals that IRE learning strategies should integrate the internalization of Islamic values, students’ potential development, and the appropriate use of educational technology. The novelty of this study lies in proposing a conceptual model of IRE learning that systematically integrates tawhid, fitrah development, character formation, and educational technology to support holistic, contextual, and insan kamil-oriented learning.